Review of Blast Loading Models, Masonry Response, and Mitigation - Eid Badshah; Amjad Naseer; Muhammad Ashraf; Feroz Shah; Kareem Akhtar (Shock and Vibration)
Different models for prediction of blast loading, response of masonry structure against blast load, and various mitigation strategies are discussed. Variation of peak positive incident pressure with scale distance in free field spherical burst and surface burst scenarios, proposed by different researchers, is presented and compared. The variation is found significant in the region of small scaled distances. Blast wave parameters in urban environment have been found different from the free field scenario. Effects of geometry, boundary conditions, and material properties on response of masonry buildings were found significant. Different mitigation strategies such as blast wall, landscaping, architecture, and retrofitting techniques are presented.